Facial Photographs and Study Models in Assessment of Orthodontic Treatment Needs: A Comparative Study - Hongal, Sudheer; Basavaraddi, Shrinivas; Patil, Gururaj; Hongal, Poornima; Basavaraddi, Vijaylaxmi (Journal of Orofacial Research, 2012)
Aim: The purpose of the study was to compare and evaluate the examiner differences when assessing orthodontic treatment needs using facial photographs and study models. Materials and methods: Thirty subjects (9 males, 21 females) who displayed a definite, severe or very severe malocclusion as per dental esthetic index scores were considered for the study. The diagnostic study models and facial photographs were assessed for each patient by two consulting orthodontists and one postgraduate orthodontic student. Visual analog scale (VAS) was used to assess. Separate assessment was made from study models and facial photographs by two orthodontists and one postgraduate student. The orthodontic treatment needs were higher from study models compared with facial photographs (p < 0.001) for all the three examiners. Results: A considerable variation in the intraexaminer and interexaminer consistency from the assessment of orthodontic treatment needs from facial photographs was shown. There were higher for orthodontic treatment needs from study models than facial photographs. Reduced intraexaminer and interexaminer variability from assessment of orthodontic treatment needs from facial photographs may suggest a specific method to achieve a more uniform evaluation of orthodontic treatment needs.